(untitled) (Fiep Bulletin - online, 2014)
Rheumatoid arthritis ( RA) is a joint disease that affects 1 % of the population , increasing significantly in women from the age of 55 and directly influencing the individuals quality of life. The aim of this study was to evaluate the association of drug or non-medication therapies on the quality of life of patients with RA. This is an observational study performed in a private clinic of rheumatology in Maringá , Paraná . Data were collected from interviews of 15 patients drug-treated and 5 patients with symptoms of RA, but not yet on pharmacological treatment, using a questionnaire ( WHOQOL - gla ) . Interviews were conducted between April and June 2013 and the data were organized and analyzed by statistical program SPSS 1.8. The results indicated that the treated group showed a total sum of 250 in overall aspects of quality of life to that compared to non-treated group, which were 222.5 . The best scores were found in the psychological and social relations in the treated group (80 and 75, respectively) and the lowest scores were found in the physical environment and the non-treated group ( 40 and 50 respectively). The physical domain that evaluates aspects such as pain, mobility, energy, fatigue and mobility to work, showed a significant impact on quality of life of these individuals. Therefore, the overall quality of life presented by treatment group are highest when compared to that of non-treated group, showing an improving in the quality of life by drug treatment